Law in the face of the problem of land take - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2020)
The aim of the considerations is to determine how the concept of land take and the related EU target of no net land take by 2050 function in the law (especially in Poland), and then to assess to what extent the perception of this formula in the law is relevant to the model of land protection and whether it has the potential to increase the effectiveness of the legal regulation in this respect. Land take is a concept that describes one of the main threats to the protection of land as an environmental resource. First attempts to incorporate this formula into the legal system of land protection have already been made. In European Union law, this was done by setting the goal of no net land take target by 2050. This objective, however, is neither binding nor specified in secondary legislation. The concept of land take and the target related to it may have a positive impact on the effectiveness of the land protection system. However, it is essential that the legal instruments are integrated and are of a binding character. The Polish legal system has reiterated the concept of indirect land take, and no national target in this respect has been adopted. This model is an example confirming the thesis that special and extensive legal regulations do not always guarantee that the protection measures are effective. Also, while it illustrates the importance of integrating individual legal regulations, it shows as well that the weaknesses of one of them (in Poland the inefficiency of spatial planning) cannot be compensated for by developed instruments in another area of law.